Ultra-Performance Liquid Chromatography-Q-Exactive Orbitrap-Mass Spectrometry Analysis for Metabolic Communication between Heart and Kidney in Adriamycin-Induced Nephropathy Rats - Chunliu Wang; Jiping Liang; Wenwen Yang; Shixiang Wang; Jie Yu; Pu Jia; Yapeng Du; Mei Wang; Ye Li; Xiaohui Zheng (Karger Publishers, 2021)
Background/Aims: Although the adriamycin-induced nephropathy model is frequently employed in the study of nephrotic syndrome and focal segmental glomerulosclerosis, the accompanying myocardial damage has always been a cause for concern. Therefore, there is a great need to study cardiorenal communication in this model. Methods: An adriamycin-induced nephropathy model was established via tail vein injection. The levels of the biochemical indicators serum albumin, serum globulin, serum total protein, serum cholesterol, serum creatinine (SCr), urinary protein, and urinary creatinine (UCr) were measured, and histopathological changes in the heart and kidneys were assessed using hematoxylin-eosin staining. Metabolomic changes in the heart, blood, and kidneys were analyzed using the metabolomics method based on ultra-performance liquid chromatography Q-Exactive Orbitrap mass spectrometry. Results: Compared with the control group, the model group showed significant decreases in serum protein and total protein levels, albumin/globulin ratio, and creatinine clearance rate as well as significant increases in serum cholesterol, SCr, urinary protein, and UCr levels. Significant pathological changes were observed in the renal pathology sections in the model group, including diffusely merged glomerular epithelial cells, inflammatory infiltration, and vacuolated glomerular cells. Additionally, thickened myocardial fibers, swollen nuclei, inflammatory infiltration, and partial myocardial necrosis could be seen in the cardiac pathology sections in the model group. Based on multivariate statistical analysis, a total of 20 differential metabolites associated with 15 metabolic pathways were identified in the heart, 7 differential metabolites with 7 metabolic pathways were identified in the blood, and 16 differential metabolites with 21 metabolic pathways were identified in the kidney. Moreover, 6 common metabolic pathways shared by the heart and kidney were identified: arginine and proline metabolism; arginine biosynthesis; glutathione metabolism; alanine, aspartate, and glutamate metabolism; beta-alanine metabolism; and histidine metabolism. Among these metabolic pathways, alanine, aspartate, and glutamate metabolism was shared by the heart, blood, and kidney. Succinic acid was found to be the key regulatory metabolite in cardiorenal metabolic communication. Conclusion: Six metabolic pathways were found to be involved in cardiorenal metabolic communication in an adriamycin-induced nephropathy model, in which alanine, aspartate, and glutamate metabolism may be the metabolic link between the heart and kidney in the development and maintenance of oxidative stress and inflammation. Succinic acid may serve as a key regulatory metabolic switch or marker of cardiac and renal co-injury, as shown in an adriamycin-induced nephropathy model.